HUBUNGAN ANTARA KONDISI KESEHATAN IBU, PELAKSANAAN IMD, DAN IKLAN SUSU FORMULA DENGAN PEMBERIAN ASI EKSKLUSIF - Dedi Alamsyah (Fakultas Kesehatan Masyarakat, Universitas Jember, 2017)
Exclusive breastfeeding means that the infant receives only breast milk. No other liquids or solids are given. Breastfeeding is influenced by a number of factors, such maternal health condition, early initiation of breastfeeding, and infant formula advertising. Data from Health Department of Kabupaten Sambas indicated that that the coverage of breastfeeding in Kecamatan Tangaran, in 2014, was 27,1% and it ranked the first of 19 districts with low coverage of breastfeeding. This study aimed at analyzing the correlation of maternal health condition, early initiation of breastfeeding, infant formula advertising, and exclusive breastfeeding in Kecamatan Tangaran Kabupaten Sambas.Using observational analytic design and cross sectional approach, this study employed 110 samples. Each variable was tested using chi square test.The results indicated that early initiation of breastfeeding (p value =0,047) has significant correlation with exclusive breastfeeding (p value=0,05). Meanwhile, maternal health condition (p value=0,071) doesn’t significantly correlate with infant formula advertising ( p value=0,606).From the findings, the health personnel are encouraged to inform the young mothers about exclusive breastfeeding, provide lactation clinic, and impose sanctions for birth attendants who do not perform early initiation of breastfeeding birth. Also pregnant women are encouraged to choose early initiation of breastfeeding birth. At last, further researcher need to have further discussion about the factors of exclusive breastfeeding. Keyword keys :Early Initiation of Breastfeeding, Exclusive Breastfeeding.